Analysis of the Level of Knowledge and Availability of Mask Waste Disposal Facilities in the Sanur Beach Area - Apriyanthi, Desak Putu Risky Vidika; Laksmita W, Ayu Saka; Widayanti, Ni Putu (GLOBAL HEALTH SCIENCE GROUP, 2024)
The COVID-19 pandemic has created new problems for the environment as evidenced by the large number of masks, both medical masks (single-use) and non-medical masks, found in public places. The discovery of masks that are discarded in any place, especially in beach tourism areas, is something we usually encounter these days. This has a negative impact on the coastal environment, in the long run, it will be one of the causes of climate change, damage to coastal ecosystems, and ecotoxicity. Sanur Tourism Area is one of the most attractive tourist attractions for tourists both domestic and foreign tourists. The aim of this research is to contribute and provide feedback to the local government especially the Sanitation and Environmental Services Department, to be more concerned about the management of mask waste and the providing of its facilities. The design of this study is descriptive to describe the level of knowledge of Sanur Beach visitors regarding the availability of mask waste disposal facilities at Sanur Beach, it is found that beach visitors have a fairly good level of knowledge (45%) in understanding the impact of mask waste disposal on tourism at Sanur Beach. The majority of respondents stated that the mask waste disposal facilities at Sanur Beach are adequate but the correct procedure for disposing of mask waste has not been found. As many as 68% of respondents stated that there is a closed landfill at Sanur Beach for mask waste disposal. The availability of facilities to manage disposable mask waste is another important factor that influences community action in implementing good waste management. For this reason, it is necessary to coordinate with relevant agencies and Sanur village officials and community cadres to negotiate to provide shared bins at several locations on Sanur Beach specifically to accommodate mask waste only to make it easier for visitors to sort their waste and not mix their mask waste again with other domestic waste.